THE CORRELATION BETWEEN THE SENSE OF BELONGING AND LEARNING MOTIVATION TOWARD THE STUDENT’S SOCIAL WELFARE - Aprianif, Aprianif; Oktavia, Oktavia; Saptono, Ari; Riyadi, Riyadi; Diananda, Amita (International Journal of Business, Law, and Education, 2023)
This research aims to see the correlation between the Sense of Belonging and the Motivation to Study and the correlation between the Sense of Belonging and Motivation to Study toward the Student's Social Welfare. This research uses causal models. The analysis technique used is SEM (Structural Equation Modeling), operated through the LISREL program. The population in this study were all active Indonesian students studying domestically. The number of samples in this study was 227 students who filled out questionnaires online. The results of this study indicate that the Sense of Belonging has a simultaneous influence on the Motivation to Study by 63%, and The Motivation to Study and the Sense of Belonging simultaneously influence the student's social welfare by 93%.